519 Diacylglycerol kinase ζ limits IL-2-dependent control of PD-1 expression in tumor-infiltrating T lymphocytes. (9th November 2020) - Arranz-Nicolas, Javier; Rodríguez-Rodríguez, Cristina; Liébana, Rosa; Leitner, Judith; Ávila-Flores, Antonia; Steinberger, Peter; Mérida, Isabel
Abstract : Background: Tumors evade T cell responses targeting them through the upregulation of tolerance-inducing mechanisms. One of the best characterized is that of PD-1/PD-1L engagement, that in healthy CD8+ T cells limits cytotoxic responses against self-antigens and that tumors employ to neutralize T cell attack. Antibody-based therapies aimed to block the PD-1/PD-1L axis have rendered notable results, but most patients eventually develop resistance. This failure is attributed to CD8+ T cells achieving an exhausted phenotype where recovery is hardly feasible. The dysfunctional phenotype of tumor-infiltrating T cells is largely triggered by the unbalance of diacylglycerol (DAG)- and Ca2+-regulated signals that results in alteration of the transcriptional T cell program. DAG kinase (DGK) ζ-dependent DAG consumption contributes to hypofunctional T cell states while DGKζ deficiency facilitates tumor rejection in mice without apparent adverse autoimmune effects. In spite of its therapeutic potential, little is known about DGKζ function in human T cells and there are not isoform-specific inhibitors targeting this DGK isoform. Methods: Here we used of a human triple parameter reporter (TPR) cell line to examine the consequences of DGKζ depletion in the transcriptional restriction imposed by PD-1 ligation. We also investigated the effect of DGKζ deficiency in the expression dynamics of PD-1, as well as the impact of the absence of this DGK isoform in the in vivo growth of a MC38 adenocarcinoma cell line. Results: We demonstrate that DGKζ depletion enhances DAG-regulated transcriptional programs, favoring IL-2 production and limiting PD-1 expression. Diminished PD-1 expression and enhanced expansion of cytotoxic CD8+ T cell populations is also observed even in the context of immunosuppressive milieus and correlates with the failure of MC38 adenocarcinoma cells to form tumors in DGKζ-deficient mice. Conclusions: Our results suggest the relevance of DGKζ as a therapeutic target on its own as well as a biomarker of CD8+ T cell dysfunctional states.